2013
DOI: 10.1016/j.jegh.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with breast cancer in Puerto Rican women

Abstract: Background Breast cancer (BC) is the most common cancer afflicting Puerto Rican women and accounts for more cancer-related deaths in this population than any other cancer. Methods Demographic, anthropometric, family history, and lifestyle data, as well as DNA repair capacity (DRC), were compared in 465 BC cases and 661 controls. Crude and multiple logistic regression-derived adjusted odds ratios were used as indicators of the associations between BC and the variables under study. Results A low DRC level, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 21 publications
3
51
0
Order By: Relevance
“…An increased risk was found in two studies, which were based on the hospital records of patients with endometriosis [9,15]. Other studies failed to prove an overall increased risk of BC among women with the disease [16][17][18][19]. In two studies, authors observed that the risk of BC was depended on age, with an excess in older women [12,20].…”
Section: Discussionmentioning
confidence: 99%
“…An increased risk was found in two studies, which were based on the hospital records of patients with endometriosis [9,15]. Other studies failed to prove an overall increased risk of BC among women with the disease [16][17][18][19]. In two studies, authors observed that the risk of BC was depended on age, with an excess in older women [12,20].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, many of the treatments for endometriosis, including oral contraceptives, analgesic use, and oophorectomy, may alter breast cancer risk (7, 10, 11). The literature are mixed regarding the relationship between endometriosis and breast cancer (2):Ten studies suggested modest positive associations between endometriosis and the risk of breast cancer with effect estimates ranging from 1.08 to 3.20 (2, 1221), four studies showed no clear association (2225), and five studies reported an inverse relationship (26–30). However, the studies conducted to date are limited by minimal control for confounding and differences in definitions of endometriosis diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has indicated that women with endometriosis may be at increased risk for several chronic diseases including cardiovascular disease and certain types of cancer, including ovarian and possibly breast (8). Epidemiologic evidence for a relationship between endometriosis and breast cancer risk has been mixed (8-11) with eleven studies suggesting modest positive associations between endometriosis and the risk of breast cancer (8, 12-21, 77), four studies showing no clear association (22-25), and five studies reporting an inverse relationship (26-30). …”
Section: Introductionmentioning
confidence: 99%